La práctica de actividades lúdicas para fortalecer el desarrollo motor fino en niñas y niños de 4 a 5 años de la escuela de educación básica Alonso de Mercadillo de la ciudad de Loja, periodo 2014-2015 - Medina Salazar, Ana Karen (2016)
This investigative work has as main title, the practice of recreational activities to strengthen the fine motor development in girls and children from 4 to 5 years of the School of Basic education Alonso de Mercadillo of the city of Loja; this has been raised as a general objective: To determine the efficacy of the practice of recreational activities to strengthen fine motor development in children from 4 to 5 years; the present investigation is of type of descriptive and correlacional study, the used methods were: inductive - deductive, analytical - synthetic, and quantitative or traditional, the skills that were used were: the survey, the test and post-test, the applied instruments are: questionnaire of the survey and the test of dexterímetro of Goodard. Procedures followed were of an institutional nature, based on the regulations of academic regime of the National University of Loja, allowing obtaining this way the corresponding permissions to develop the investigation. The population with whom one worked there were three teachers of the initial level two A, B, and C and 23 girls and children of the initial level parallel two C, of the School of Basic education Alonso de Mercadillo. For the present investigation it has ended: That it is necessary to work with recreational activities like the games of construction and those of skill and workmanship, because they allow boys and girls from 4 to 5 years to acquire a basic engine development for their age; and that the recreational activities must be used like methodological hardware, because they benefit the development of the different evolutionary areas of the child, especially the motor area which is fine, which happened with the results obtained in the post-test.